Perceived effectiveness of social media platforms for HIV and AIDS information communication among university undergraduates in south-west Nigeria (2017)
The study examined the perceived effectiveness of social media on HIV and AIDS communication among undergraduates in southwest Nigeria. Data was obtained through the administration of 355 copies of structured questionnaire to respondents in University of Lagos, Obafemi Awolowo University and University of Ibadan. Data obtained was analysed using tables, simple percentages and bivariate regression analysis. The results showed that awareness of social media enabled 71.3% of the respondents to use social media sites. Out of this percentage, it enabled 27% to interact; 25.1% to exchange ideas, 11.3% to be informed on HIV and AIDS, and 7.9% stated increased knowledge on HIV. The result further showed that 90.7% of the respondents stated that HIV and AIDS information on social media platforms was very useful. Result showed that 23.7% of the male and female respondents had sexual intercourse 3 months ago, out of this, 10.2% used a condom (s), while 13.5% did not make use of condom. Despite this high level of awareness, regression result showed that sharing of HIV and AIDS information on social media did not have significant influence on condom use (F = 2.586, p>0.05). The study suggested that HIV and AIDS communication on social media should prioritize basic messages such as encouraging use of condoms and other prevention methods.